Evaluation of Silicon Carbide Nanoparticles as an Additive to Minimize Surfactant Loss during Chemical Flooding. Issue 22 (9th June 2022) - Pandey, Anurag; Roy, Vishnu; Kesarwani, Himanshu; Sharma, Shivanjali; Saxena, Amit
Abstract: Surfactant flooding is a prolific enhanced oil recovery technique. It alters the rock fluid interfacial interactions between reservoir fluids and rocks. However, a pair of impeding factors often limit the economic viability of the process and need to be optimized. The first is the surfactant loss on the adsorbent surface due to adsorption making it a potential environmental problem. The second is the Critical Micelle Concentration (CMC) which governs the amount of surfactant pumped. This study aimed to minimize the surfactant loss and the CMC, thereby optimizing the flooding efficiency and reducing the environmental concerns for nanoparticle applications. To achieve this, Silicon Carbide nanoparticles (SCN) were employed as additives to the surfactant solution. It was observed that the use of SCN reduces the surfactant adsorption by as much as 44 % and the critical micelle concentration by 14 %. The studies also observed that the concentration of SCN required to get these results is dramatically (more than 25 times) lower than previously reported literature on other nanoparticles. To adsorption isotherm studies provide an insight into the type of adsorption taking place. The adsorption isotherm follows the Langmuir model. Abstract : This work involves the application of the SCN nanoparticles with surfactants to reduces the surfactant adsorption into the sand. In the oil recovery process from matured oil fields, the surfactant has the potential to be exploited as an oil mobilising agent. The SCN nanoparticles along with surfactants showed promising results of adsorption, surface tension, contact angle and oil recovery.